“Pharmacological” analysis of atrial fibrillation maintenance mechanism: reentry, wavelets, or focal? - Alexander Burashnikov (Frontiers in Cardiovascular Medicine)
The primary electrophysiological mechanism of atrial fibrillation (AF) maintenance is poorly defined. AF mapping studies readily record focal activations (defining them as focal sources or breakthroughs) and “incomplete reentries” (defining them as reentries or would-be-reentries) but do not or rarely detect complete circular activations. Electrophysiological alterations induced by anti-AF drugs before AF cardioversion may help delineate the mechanism of AF maintenance. Cardioversion of AF by antiarrhythmic drugs is associated with prolongation of the AF cycle length and temporal excitable gap (t-EG), resulting in improvement in AF organization (AF-org), and with or without alterations in the refractory period, conduction velocity and wavelength. Such electrophysiological pattern is conceivable with termination of a single focal source but not a single reentry (Class III agents do not increase reentrant t-EG). Yet, a single focal source and multiple focal sources are plausible as the primary mechanism of AF maintenance prior drug administration. Improvement in AF-org caused by anti-AF agents before AF cardioversion is coherent with simultaneous multiple random reentries and wavelets. However, simultaneous multiple reentries are unlikely to occur regularly (most of the contemporary AF mapping studies report either a single reentry at a time or no reentry at all), and the ability of random wavelets to maintain AF is speculative. The conducted analysis inclines toward the focal source as the primary mechanism of AF maintenance.